Analysis of Teacher Roles and Student Problem Solving Skills in Learning Physics Online Collaborative Problem Solving - Lurinda, Nadia Wahyu; Nugroho, Sunyoto Eko; Khumaedi, Khumaedi (Universitas Negeri Semarang, 2022)
The development of education needs to adapt to the needs of 21st century skills, including collaboration and problem solving. This study aims to analyze and describe the profile of Collaborative Problem Solving (CPS) online learning, as well as to describe the problem solving skills after learning. This research was conducted at SMA N 1 Gubug in class XI MIPA 1 for the academic year 2021/2022 with a qualitative descriptive method. CPS online learning is divided into virtual meetings using Microsoft Teams and discussions via text messages in WhatsApp. The research data was obtained through data observation’s, interviews, and written posttests. Data processing using a fixed comparison method with three stages, namely; data reduction, categorization, synthesis, and determination of hypotheses. The results showed that the role of the teacher appeared with almost the same frequency, namely as a motivator (37%), communicator (32%) and facilitator (31%). Students' problem-solving skills are dominated by the ability to plan and identify problems with the frequency of occurrence of 35% and 31%, respectively. The next two stages of problem solving, namely implementing the plan and checking back only appeared with a percentage of 19% and 15%.